Evidence-based policing: uses, benefits and limitations - Heyer, Garth den (Springer, 2022)
1. Introduction -- 2. What is Evidence-based Policing? -- 3. Developments in the use of Evidence-Based Policing in the United Kingdom -- 4. The use of evidence-based practices in the health and social sectors -- 5. The arguments for and against using Evidence-based Policing -- 6. Alternative crime response strategies to Evidence-based Policing -- 7. Assessing the receptivity of Evidence-based Policing -- 8. The use of Evidence-based Policing by five police departments in the United States -- 9. How can Evidence-based policing be improved? -- 10. Conclusions.